Membangun Kesejahteraan Masyarakat Indonesia Sehat : Strategi Komprehensif dalam Pencegahan Penyakit, Reformasi Sistem Kesehatan, dan Peningkatan Kesadaran Isu Kesehatan Mental - Violetta Hosiana Christella Silalahi; Bernique Kasih Friscilla Purba; Ribka Angelina Sihombing (Jurnal Cakrawala Akademika, 2024)
. Indonesia faces various challenges in its health system, including the burden of communicable and non-communicable diseases, as well as low public awareness of mental health. In addition, uneven quality and access to health services is a significant problem. This research aims to formulate a comprehensive strategy in disease prevention, health system reform, and mental health awareness to improve community welfare. This research approach uses a qualitative descriptive method with literature studies, which analyzes various academic sources such as scientific journals, policy reports, and official government documents. The results show that although programs such as the National Health Insurance (JKN) have increased access to health for the public, there are still challenges such as budget deficits, uneven distribution of health workers, and lack of adequate mental health services. Disease prevention strategies through primary, secondary, and tertiary approaches need to be strengthened, especially in rural areas. In addition, the integration of physical and mental health services is the key to improving the welfare of the community holistically. In conclusion, a holistic approach is needed in health system reform, including strengthening mental health regulations, more intensive health promotion, and improving the quality and access to health services throughout Indonesia.